2008
DOI: 10.1136/ard.2008.099861
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and toxicity of methotrexate (MTX) monotherapy versus MTX combination therapy with non-biological disease-modifying antirheumatic drugs in rheumatoid arthritis: a systematic review and meta-analysis

Abstract: Objective:To evaluate the efficacy and toxicity of methotrexate (MTX) monotherapy compared with MTX combination with non-biological disease-modifying antirheumatic drugs (DMARDs) in adults with rheumatoid arthritis.Method:A systematic review of randomised trials comparing MTX alone and in combination with other non-biological DMARDs was carried out. Trials were identified in Medline, EMBASE, the Cochrane Library and ACR/EULAR meeting abstracts. Primary outcomes were withdrawals for adverse events or lack of ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
83
0
15

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(103 citation statements)
references
References 126 publications
0
83
0
15
Order By: Relevance
“…LD-MTX was recently reported to be an inhibitor of lymphocyte proliferation and the destructive capacity of leukocytes that reach the inflammatory area (14). It also promotes extracellular adenosine accumulation at the inflammatory site, which inhibits some cytokines, superoxide, nitric oxide, and TNF-α (14,15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LD-MTX was recently reported to be an inhibitor of lymphocyte proliferation and the destructive capacity of leukocytes that reach the inflammatory area (14). It also promotes extracellular adenosine accumulation at the inflammatory site, which inhibits some cytokines, superoxide, nitric oxide, and TNF-α (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…It also promotes extracellular adenosine accumulation at the inflammatory site, which inhibits some cytokines, superoxide, nitric oxide, and TNF-α (14,15). Adenosine is a cytoprotective molecule due to its inhibitor effect on toxic oxygen metabolites created from the adhesion of stimulated neutrophils to the endothelium (11,16).…”
Section: Discussionmentioning
confidence: 99%
“…[1] Recently, low-dose methotrexate (MTX) has become the mainstay in the treatment of some inflammatory diseases such as rheumatoid arthritis. [3,4] Chronstein et al [3] showed that low-dose MTX can inhibit both proliferation of lymphocytes in an inflammatory exudate and reduce the destructive capacity of the leukocytes that do arrive at the inflammation site. Although its exact mechanism of action has not been clarified yet, low-dose MTX promotes extracellular adenosine accumulation at the inflammation sites.…”
Section: Sonuçmentioning
confidence: 99%
“…Methotrexate in rheumatoid arthritis has shown robust on-label evidence for e cacy over the years [3]. Aspirin, developed as a painkiller more than 100 years ago, is nowadays widely and successfully used in cardiology and neurology, and can perhaps in the near future be used to decrease the risk of developing cancer [4].…”
Section: Examples Of Drug Rediscoverymentioning
confidence: 99%